The effect of small-sided games (S.S.G) according Lactic Acid System times to develop some physiological, physical conditions and compound skills in male youth football players - Ahmad, Ass.prof.Dr. Hawkar Salar; Abas, L.Dr. Zia Adl; Abdulmanaf, Ass.prof.Dr. Yassin (Sulaimani Journal for Humanities, 2025)
The use of Small-Sided Games (S.S.G) in football has become a modern method to improve the level of football players in many aspects, so studying and applying it to determine its benefit on the physical, functional and skill aspects is necessary. The study aims to: Identify the effect of SSG exercises according Lactic System times to develop some physiological, physical conditions and compound skills in male youth football players. The study used the experimental method due to its suitability to the nature of the study. The study subjects consisted of (28) football players representing the youth of Ashti Sports Club. The subjects were divided into two groups, an experimental group and a control group, with (14) players for each group. The training program was applied to the experimental group for a period of 8 weeks, with two training sessions given in the main section of the training session. The results of the study showed that the players in the experimental group improved their physical and functional abilities and compound skills due to their use of S.S.G exercises. Among the most important recommendations: Emphasizing the importance and necessity of using S.S.G exercises frequently, scientifically, and accurately in training football players, based on Lactic System times, and paying attention to developing them as they are one of the most important modern exercises in our time that football players need. In addition, Small-Sided Games (S.S.G) soccer exercises according to the anaerobic-lactic system times contributed to improving the physical capabilities (fitness level) and raising the functional level (maximum oxygen consumption "Vo2max") of the experimental group members for the post-tests.
Keywords: Complex skills; SSG; VO2max; lactic system; heart rate